Analysis of Green Finance Implementation at BCA Syariah - Okta Sari; Muhammad Iqbal Fasa (Scimadly Publishing, 2024)
Today, the overuse of technology has posed severe challenges to economies around the world. The purpose of this study was to determine the concept of Green finance and measurement indicators used and to determine the policies that have been applied in the implementation of the concept of Green finance at Bank BCA Syariah. This article uses the literature review method which uses a qualitative approach to review various literature sources, including scientific journals, reports from related institutions or companies, and Green finance related policies. This study uses descriptive analysis method on various research related to the concept and implementation of Green finance. The results of the study show that bank BCA Syariah has implemented several Green Finance programs from 2019 to 2023, including the implementation of green principles with green financing, the use of water, paper, waste treatment, strategic cooperation in the scope of Sustainability, Policy and planning related to environmental-based sustainability.